住院营养不良儿童出院后营养恢复状况分析 (Zhongguo Dang Dai Er Ke Za Zhi, 2020)
OBJECTIVE: To investigate the nutritional recovery status of children with moderate or severe malnutrition during hospitalization after discharge. METHODS: The children with moderate or severe malnutrition were given nutrition support during hospitalization. They received a regular follow-up and nutrition guidance after discharge. The weight-for-age and height-for-age Z-scores reaching above -2SD were considered the nutrition criterion for ending follow-up. RESULTS: Among the 298 children with moderate or severe malnutrition, 174 (58.4%) reached the criterion for ending follow-up, 100 (33.6%) were lost to follow-up, 18 (6.0%) died, and 6 (2.0%) did not reach the criterion for ending follow-up after 18 months of follow-up. The children with malnutrition in the department of surgery had a significantly higher proportion of children reaching the criterion for ending follow-up than those in the department of internal medicine (P < 0.05). The children with severe malnutrition had a significantly higher loss to follow-up rate than those with moderate nutrition (P < 0.05). The majority of children with emaciation reached the criterion for ending follow-up at month 3 after discharge, while those with growth retardation reached such the criterion at months 3-6 after discharge. Up to 1 year after discharge, more than 80% of the children with different types of malnutrition reached the nutrition criterion for ending follow-up. CONCLUSIONS: Most of the children with malnutrition who adhere to follow-up can reach the expected nutrition criterion within 1 year after discharge. The children with growth retardation have slower nutritional recovery than those with emaciation.